Photochemical and essential oil analysis in citronella after cutting of the root system and shoot (Revista Brasileira de Plantas Medicinais, 2020)
Citronella grass has repellent activity, fungal and bactericidal action due to the action of its essential oil. Thus, the objective was to compare the photochemical capacity with the production of essential oil in citronella plants submitted to different levels of cuts in the aerial part and in the roots. The experiment had a completely randomized design with five treatments (0, 25, 50, 75 and 100%) of cuts in the roots, with 1 cut in the aerial part and 2 cuts in the aerial part, with 4 replicates. Transient OJIP fluorescence assays and chloroplastidic pigments were performed for the different treatments. For extracting the essential oils, the plant material was collected after different dates. For the chlorophyll a fluorescence data on citronella plants after 30 days of root and leaf cut and 165 DAC, all of these treatments remained above the control for the PIabs and PItotal parameters, which reflect the performance index, thus indicating the plants for this period. In relation to the essential oil, the three substances found in the highest proportion were β-citronelal, β-citronelol and trans-geraniol, and the treatment with the highest yield of essential oil did not contain any cuts. Thus, it was verified that for these three substances analyzed there is no need to perform thinning at the root nor cuts in the leaves.